Local Wisdom Themes in Project for Strengthening the Profile of the Pancasila Student: A New Perspective on Science Learning in Junior High School - Arti, Yuli; Widowati, Asri (Journal of Science Education Research, 2025)
The research aimed to analyze science learning through the implementation of the Project for Strengthening the Profile of Pancasila Student (P5) with local wisdom theme in Junior High School (SMP). The focus of the study was to explore the methods, employed within the Project for Strengthening the Profile of Pancasila Student framework. Also, it aimed to analyze the science learning processes during these activities, particularly in relation to local wisdom themes. Data were collected from 97 students in grades VII, VIII, and IX at SMP PIRI 1 Yogyakarta through observations on November 28, 2023, and simple interviews with students and teachers to collect feedback on the Project for Strengthening the Profile of Pancasila Student activities. The local wisdom theme was "Batik." The activities commenced with a Duha prayer and an opening session, followed by the presentation of batik material, group divisions, and the process of creating batik designs. The process incorporates the application of scientific concepts, such as biodiversity and changing in states of matter, and mixtures. The findings indicate that the application of the P5 framework with a local wisdom theme enhances students’ understanding of scientific concepts and their engagement in learning. It is hoped that these findings will contribute to the development of more contextual and relevant teaching methods. The research used qualitative research with an interview. The interview instrument was developed by determining the objective of the interview, formulating the activities or aspects, arranging the indicators, and conducting the interview. Data analysis was carried out by synthesizing the data from interviews.